2018
DOI: 10.1029/2018ef000937
|View full text |Cite
|
Sign up to set email alerts
|

Future Global Soil Respiration Rates Will Swell Despite Regional Decreases in Temperature Sensitivity Caused by Rising Temperature

Abstract: Between 1960 and, the global soil respiration (R SG ) flux increased at a rate of 0.05 Pg C year À1 ; however, future increase is uncertain due to variations in projected temperature and regional heterogeneity. Regional differences in the sensitivity of soil respiration (R S ) to temperature may alter the overall increase in rates of R S because the R S rates of some regions may decelerate while others continue to rise. Using monthly global R S data, we modeled the relationship between R S and temperature for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 73 publications
1
34
1
Order By: Relevance
“…We suspect that the common decision not to measure during the dormant season and to instead extrapolate nonwinter measurements to an annual flux) results in significant “missed” variability. Significant numbers of studies estimate annual R S from growing‐season only fluxes (Jian et al, ), and the errors on these estimates are almost certainly larger than ones based on full‐year sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that the common decision not to measure during the dormant season and to instead extrapolate nonwinter measurements to an annual flux) results in significant “missed” variability. Significant numbers of studies estimate annual R S from growing‐season only fluxes (Jian et al, ), and the errors on these estimates are almost certainly larger than ones based on full‐year sampling.…”
Section: Discussionmentioning
confidence: 99%
“…We also suggest that it enables better standards for reporting R S , specifically with respect to errors associated with temporally sparse data sets (Jian, Steele, Day, Quinn Thomas, & Hodges, ). This should allow us to better distinguish natural variability from measurement error, provide benchmarks for confidently ascribing observed changes in R S to climatic drivers (Bond‐Lamberty & Thomson, ), and enable more accurate estimation of spatially and temporally upscaled fluxes (Jian, Steele, Day, & Thomas, ). For example, studies with limited data might apply some standard amount of uncertainty based on the CV distributions shown in Figure (although rigorously defining and applying data reporting standards for such an approach would require a consensus among the soil research community).…”
Section: Discussionmentioning
confidence: 99%
“…Daily fluxes were calculated by multiplying the measured hourly flux by 24, given that fluxes measured between 08:30 and 11:20 were found to be representative of the mean daily flux (Yang et al 2017). Sampling in the morning hours has been shown to minimise the effect of soil temperature in soil respiration (Jian et al 2018). Research in forests and in rangelands in Kenya showed a negligible effect of soil temperature on CH 4 fluxes (Werner et al 2007;Zhu et al 2018).…”
Section: Gas Sampling and Analysismentioning
confidence: 99%
“…This simulation performance is better than that found in previous studies. For example, 11 soil respiration model studies at national, regional, and global scales (presenting predictable proportions of 26-68%) were reviewed by Chen et al [41], and previous work has been conducted on soil respiration simulation in China (RMSE = 799 g CO 2 m −2 yr −1 [42]) and on global soil respiration [3,43,44]. The simulation error of soil CH 4 fluxes using the present method also demonstrates a better simulation accuracy, yet it has rarely been discussed on an annual scale (RMSE = 76 g CH 4 m −2 yr −1 [45]).…”
Section: Feasibility Of Estimating Af Using Low-frequency Flux Data Omentioning
confidence: 99%